2015
DOI: 10.1097/mjt.0b013e31826fc4ec
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mean Arterial Blood Pressure During Sildenafil Use in Neonates With Meconium Aspiration Syndrome or Sepsis

Abstract: The aim of this study was to evaluate changes in mean blood pressure (MBP) in late preterm and term newborns with meconium aspiration syndrome (MAS) or sepsis who, in addition to inhaled nitric oxide (iNO), received enteral sildenafil for treatment of persistent pulmonary hypertension of the newborn. Data on sildenafil dosing, MBP, and vasopressor/inotrope use were collected for 72 hours after initiation of sildenafil. Groups were compared between "low dose" (<3 mg·kg·d) versus "high dose" (≥ 3 mg·kg·d) and "e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The change in the mean arterial blood pressure during sildenafil use in neonates with meconium aspiration syndrome or sepsis was assessed in a retrospective study. No significant decrease in mean blood pressure or increase in vasopressor/inotrope requirement occurred (42). Furthermore, none of the three randomized controlled trials on the use of sildenafil for PH of infants reported a decline in the blood pressure (2528).…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…The change in the mean arterial blood pressure during sildenafil use in neonates with meconium aspiration syndrome or sepsis was assessed in a retrospective study. No significant decrease in mean blood pressure or increase in vasopressor/inotrope requirement occurred (42). Furthermore, none of the three randomized controlled trials on the use of sildenafil for PH of infants reported a decline in the blood pressure (2528).…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…1 Nevertheless, sildenafil has been associated with ROP and hypotension in neonates and increased mortality at high doses in children older than 1 year. 38,39,42 Even with these side effects in mind, limited treatment options with their own toxicities and the availability of an oral formulation of sildenafil that can be administered in an outpatient setting make it an appealing option.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,13,21,[23][24][25][26][27][28][29][30] Reported adverse effects of sildenafil in infants include severe systemic hypotension and increased incidence of retinopathy of prematurity (ROP), but none has been consistently reported. 13,28,[30][31][32][33][34][35][36][37][38][39] In this study, we describe the frequency of use of sildenafil in a large number of neonatal intensive care units (NICUs), the change in prescribing patterns from 2001 to 2016, the diagnoses and interventions associated with sildenafil use, and the occurrence of in-hospital morbidity and mortality.…”
mentioning
confidence: 99%
“…19,20 Despite this perceived pulmonary selectivity, systemic hypotension can occur because of direct passage of sildenafil into the systemic circulation through intra-and extra-cardiac shunts, due to direct negative effects of sildenafil on the neonatal myocardium, or as a result of variable levels of type-5 phosphodiesterase expression in the lungs with the potential for off-target effects. 9,21 Treatment-related systemic hypotension was first reported in 5 of 36 (14%) infants >34 weeks gestational age exposed to escalating doses of sildenafil via intravenous infusion. 7 These findings are comparable to the 10% prevalence of hypotension found in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Findings from previous studies evaluating sildenafil's safety in infants are contradictory. 5,[7][8][9][10] These findings may be due to differences in dosing and drug exposure, as evidenced by the wide range of observed plasma concentrations of sildenafil in previous pharmaco kinetic studies. 11,12 Because of this variability, a complete investigation of the cardiovascular safety profile of sildenafil in infants will require evaluation of drug dosing and exposure.…”
Section: S Ildenafil Is a Potent Type-5 Phosphodiesterasementioning
confidence: 99%